ChemInform Abstract: Synthesis of Osthole Derivatives with Grignard Reagents and Their Larvicidal Activities on Mosquitoes. Issue 18 (April 2016) - Liu, Ming; Liu, Yang; Hua, Xuewen; Wu, Changchun; Zhou, Sha; Wang, Baolei; Li, Zhengming
Abstract: The structure of osthole (IIIa) is modified to improve the larvicidal activity against mosquitoes.